Implementasi Akuntansi Kombinasi Bisnis Sebelum Dan Setelah Adopsi IFRS Di Indonesia (Studi Konseptual) - Ayu Rofi Widayanti (AKUNTANSI 45, 2023)
The purpose of this research is to compare and contrast how business combination accounting was practiced in Indonesia before and after the country adopted IFRS. This study is categorized as qualitative and makes use of content analysis methods. The data used is secondary data, in the form of previous research articles, literature studies that have a relationship with the topic of discussion in this study. The previous research criteria, namely research in 2010, 2011, 2015, and 2018, because it aligns with the most recent requirements of PSAK 22, which are convergent IFRS for businesses engaging in mergers and acquisitions. The findings demonstrated that goodwill amortization and negative goodwill recognition were still present in financial reporting by enterprises prior to the IFRS convergence in PSAK 22. Minority (non-controlling) interests are still calculated by the corporation using the book value of its assets. When a firm adopts IFRS, it must revise its financial statements to reflect the new accounting standard's implications for the kind and amount of equity-classified contingent consideration. Goodwill is not re-amortized, but it is included in the investment's impairment test and reflected in the income statement. Then, in accordance with PSAK 22, a separate identification will be made for non-controlling interests in subsidiaries, which will include both the amount of non-controlling interests at initial recognition and the fraction of non-controlling interests for subsequent changes in equity.